Verbal Representation of Lies in Russian and Anglo-American Cultures. (14th December 2016) - Potapova, Rodmonga; Lykova, Olga
Abstract: A number of researchers maintain that certain differences exist in the way lies are represented verbally in Russian and Western cultures. While Russian dictionaries tend to place particular emphasis on the immoral nature of lies, American ones underscore their illegality. The overall aim of this study is to analyze peculiarities of the conception of lying in these cultures. The study is based on the comprehensive analysis of 240 fragments from Russian and Anglo-American literature that describe lies and their realization. The results show that Russian people have a unique conception of lying that differs greatly from those of Western cultures.